2020
DOI: 10.1088/1361-6587/abb0f7
|View full text |Cite
|
Sign up to set email alerts
|

Electronegative magnetized plasma sheath properties in the presence of non-Maxwellian electrons with a homogeneous ion source

Abstract: The three-fluid model was employed to study electronegative magnetized plasma sheath properties in the presence of non-Maxwellian electrons. The Bohm condition for the electronegative magnetized plasma was extended in the presence of a homogeneous ionization source term and an ion-neutral collision force. The effect of the following physical parameters: the degree of non-Maxwellian electrons, ion-neutral collisions, obliqueness of the magnetic field and source frequency on the plasma sheath parameters are nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…A good number of studies have been carried out to explore sheath physics by assuming non‐extensive electron distribution. [ 25–30 ] These studies have reported that deviation of electron distribution from the Boltzmannian nature leads to variations in the space charge deposition near the wall. Moreover, expansion of the sheath has also been observed for lower values of q$$ q $$.…”
Section: Introductionmentioning
confidence: 99%
“…A good number of studies have been carried out to explore sheath physics by assuming non‐extensive electron distribution. [ 25–30 ] These studies have reported that deviation of electron distribution from the Boltzmannian nature leads to variations in the space charge deposition near the wall. Moreover, expansion of the sheath has also been observed for lower values of q$$ q $$.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a positive barrier is formed at the surface; however, it is also possible to produce negative charge barrier near to the positively biased electrode. In recent years, many experimental and theoretical works on electronegative plasma sheath with different models have been reported (Kono 2003, Hatami, Shokri & Niknam 2008, Shaw, Kar, & Goswami 2012, Jing-ju, Ma & Wei 2013, Basnet, Patel & Khanal, 2020 but still, it is not fully understood. It has applications in diverse fields such as plasma etching, surface treatment, ion implantation, fabrication of semiconductor devices, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[3]. The plasma sheath is one of the oldest problems in plasma and in recent years, the sheath formed between magnetized plasma and a particle absorbing wall has received a considerable amount of attention [2,[4][5][6][7][8][9]. R. Chodura was the first to consider effect of magnetic field in the sheath region, and modified the Bohm criterion, which was earlier valid only for non-magnetic cases [1,10].…”
Section: Introductionmentioning
confidence: 99%
“…magnetic field dependent region and electric field dependent region where the magnetic field and the electric fields, respectively, are dominant. Basnet et al studied sheath properties in the presence of non-Maxwellian electrons in case of electronegative magnetized plasma [5]. They were able to extend the Bohm condition for the electronegative magnetized plasma.…”
Section: Introductionmentioning
confidence: 99%